Spontaneous Splenic Rupture following Colorectal Surgery and Hemodialysis - Ahmed Mohammed AlMuhsin; Antonio Privitera; Ameera Balhareth; Khalid Sabr (Case Reports in Surgery)
Atraumatic splenic rupture is rarely encountered in clinical practice compared to traumatic rupture. General risk factors include hematological, infectious, or malignant splenic diseases, uremic coagulopathy, use of heparin, hypertension, and immune-compromised status. Spontaneous splenic rupture following colorectal surgery has never been reported. Maintaining a high index of suspicion in patients presenting with left upper quadrant pain and tenderness is crucial. Diagnosis can be made with the aid of an ultrasound or CT scan. The management plan should be tailored to the patient’s clinical conditions. The authors present a case of spontaneous splenic rupture in a patient following colectomy for cancer and undergoing postoperative hemodialysis and discuss the possible etiological factors.